Effectiveness of Pemafibrate Dose Escalation on Metabolic Dysfunction-Associated Steatotic Liver Disease Refractory to Standard Dose - Satoshi Shinozaki; Kouichi Miura; Toshiyuki Tahara; Hironori Yamamoto (Metabolites, 2025)
Background and Aim: Controlling the hepatic inflammation of metabolic dysfunction-associated steatotic liver disease (MASLD) is important to prevent serious condition. Pemafibrate, a selective peroxisome proliferator-activated receptor-α modulator, has demonstrated effectiveness at a standard dose (0.2 mg daily). The aim of this study is to evaluate the effectiveness of pemafibrate dose escalation from 0.2 mg to 0.4 mg daily in patients with MASLD who are refractory to standard-dose therapy. Methods: This study included patients with MASLD who had a persistent elevation of alanine aminotransferase (ALT) levels despite more than one year of standard-dose pemafibrate therapy (0.2 mg daily). All patients underwent dose escalation to 0.4 mg once daily. Hepatic inflammation was assessed using serum ALT levels, hepatic function was evaluated with the albumin–bilirubin score, and hepatic fibrosis was estimated using Mac-2 binding protein glycosylation isomer (M2BPGi) levels. A one-year treatment period was investigated, including six months before dose escalation and six months after dose escalation. Results: Eleven patients were included. The median treating period with standard-dose pemafibrate was 3.2 years. Weight did not show significant change throughout the observation period. Regarding the hepatobiliary enzyme, the aspartate aminotransferase, ALT, and γ-glutamyl transpeptidase levels significantly improved six months after the dose escalation. Specifically, ALT improved in all patients, and the ALT levels normalized in four patients (36%). The lipid profiles, the albumin–bilirubin score, and M2BPGi did not significantly change after the dose escalation. Conclusions: The dose escalation of pemafibrate from 0.2 mg to 0.4 mg daily may improve hepatic inflammation in patients with MASLD refractory to standard-dose therapy.